2005
DOI: 10.1677/jme.1.01703
|View full text |Cite
|
Sign up to set email alerts
|

IGF-I and vasoactive intestinal peptide (VIP) regulate cAMP-response element-binding protein (CREB)-dependent transcription via the mitogen-activated protein kinase (MAPK) pathway in pituitary cells: requirement of Rap1

Abstract: In previous studies we demonstrated that vasoactive intestinal peptide (VIP) mediation, and interactions between mitogen-activated protein kinase (MAPK) and cAMP/protein kinase A (PKA) signaling pathways are implicated in insulin-like growth factor I (IGF-I)-and VIP-induced lactotroph proliferation. These facts led us to investigate the intracellular mechanisms involved in IGF-I-and VIP-induced lactotroph proliferation. Exposure of cultured male rat pituitary cells to IGF-I (10 −7 M) or VIP (10 −7 M) stimulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 59 publications
(29 reference statements)
3
17
0
Order By: Relevance
“…4B), reflecting the targeted activation of Star gene expression in response to the peptidergic stimulation. This observation may mirror the pituitary, where previously published observations showed that VIP could strongly induce the phosphorylation of CREB (Fernandez et al, 2005). This data pairs well with the results from our real time PCR and promoter activity data indicating that incubation of KK1 and primary granulosa cells with VIP strongly induced Star promoter activity, resulting in mRNA levels comparable to those observed in response to dbcAMP.…”
Section: Discussionsupporting
confidence: 64%
“…4B), reflecting the targeted activation of Star gene expression in response to the peptidergic stimulation. This observation may mirror the pituitary, where previously published observations showed that VIP could strongly induce the phosphorylation of CREB (Fernandez et al, 2005). This data pairs well with the results from our real time PCR and promoter activity data indicating that incubation of KK1 and primary granulosa cells with VIP strongly induced Star promoter activity, resulting in mRNA levels comparable to those observed in response to dbcAMP.…”
Section: Discussionsupporting
confidence: 64%
“…These active integrin subunits then signal to the Rho family of GTPases leading to actin reorganization [168]. Chemokines such as stromal derived factor-1 (SDF-1) and insulin-like growth factor-1 (IGF-I) stimulate Rap1 activation and integrin-mediated binding to endothelial cells [169,170]. In endothelial cells, Rap1 is involved in the maintenance of junctions and decreased Rap1 activation leads to retraction of VE-cadherin and junction disassembly [171,172].…”
Section: Rho Gtpases In Extravasationmentioning
confidence: 99%
“…Plasmids pRL-TK, which contains a cDNA coding for Renilla, was used to monitor transfection efficiency. The reporter constructs used were: pNIS-2.8-Luc, which contains a 2.854-bp DNA fragment of the rat NIS promoter (33), hTGenh/prm-Luc, which contains the human Tg promoter/enhancer (64), and 3xCRE-Luc, which contains three CREs in tandem (65). Nterminal FLAG-tagged human G-protein ␤1 subunit and Nterminal HA-tagged human G-protein ␥2 subunit, cloned into pcDNA3.1ϩ, were obtained from the Guthrie cDNA Resource Center (Sayre, PA).…”
Section: Fig 9 G␤␥ Effect On Pax8 Localizationmentioning
confidence: 99%